Influence of dietary Salicornia europaea L. extract supplementation on feed efficiency of Altay sheep by modifying their gastrointestinal bacteria communities - Kamal, Mahmoud; Lele, Wang; Shuzhen, Tang; Jiandi, Liang; Rongyan, Qin; Yanfeng, Liu; Wenqi, Wang; Xiangyu, Chen; Cheng, Yanfen (Frontiers in Microbiology, 2024)
This experiment aimed to examine the impact of Salicornia europaea L. extract on sheep growth performance, rumen fermentation variables, nutrient apparent digestibility, and gastrointestinal microbial diversity. Forty-eight male Altay sheep, weighing 32.5 ± 2.8 kg and approximately 3.5 months old, were chosen. Four dietary treatments, each consisting of four replicates and three sheep per replicate, were distributed randomly to the sheep. The pelleted total mixed ration containing Salicornia europaea L. extract at 0.0, 0.2, 0.4, and 0.6% DM was freely available to the sheep in the four treatment groups. The 56-day experiment consisted of 45 days of measurements followed by 11 days of adaptation. The growth performance was not affected by nutrition Salicornia europaea L. extract (P≤0.05), but the feed-to-gain ratio was reduced when the extract was given at 0.4% DM (P≤0.05). Compared to the 0% and 0.2% treatments, the apparent digestibility of DM, OM, NDF, and ADF was substantially greater in the 0.4%, and 0.6% treatments. Furthermore, compared to sheep in the 0% and 0.2% groups, sheep in the 0.6% group had a noticeably higher apparent digestibility of CP. As the amount of Salicornia europaea L. extract added to the rumen fluid rose, the molar ratio of acetic acid increased. In contrast, the molar ratio of propionic acid gradually decreased, and the total volatile fatty acid content gradually reduced. Thus, adding a suitable quantity of Salicornia europaea L. extract to the sheep ration is natural and secure, which may improve the environmental sustainability of small ruminant production systems.